¬¬¬VIABILITAS BAKTERI ASAM LAKTAT (BAL) YANG DIISOLASI DARI KULIT ARI KACANG KEDELAI TERHADAP GARAM EMPEDU (Oxgall) DAN ASAM KLORIDA (HCl) - Febria Martina Sari; Evy Rossi; Raswen Efendi (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
The purpose of this study was to determine the viability of isolatesof Lactic Acid Bacteria (LAB) isolated from ari skin soybean extract against hydrochloric acid (HCl) and bile salts (oxgall). This research was conducted experimentally and the data obtained was tabulated and analyzed descriptively. The treatments in this study were MRS Broth having pH adjusted by additionof chloride acid to 2.5 and 3 incubated at 37°C for 0and 1.5 hours,MRS Broth without addition of bile salt (oxgall) with 0.5% concentration,and MRS Broth medium with the addition of bile salts (oxgall) witha concentration of 0.5% incubated at 37°C for 0 and 5 hours.The results of this study showedthatisolateLactobacillusK.11.3, Lactobacillus K.12.1, Lactobacillus K.22.2 could to survive with viability around 96.40, 96,74 and 96.17% on pH 2,5, while at pH 3 each isolate had 99.44, 99.10, 98.65%viability which was incubated for 1.5 hours.Isolates LactobacillusK.11.3,Lactobacillus K.12.1, Lactobacillus K.22.2 could survive on media containing0.5g of oxgall and had viability of98.31, 98,20, 97.97% incubated for 5 hours. Keywords: viability, lactic acid bacteria, Chloride acid, oxgall.